Broadening the Scope of Bone Anvils: Direct AMS 14C Dating from the Island of Menorca (Western Mediterranean). Issue 1 (14th December 2016) - Valenzuela, Alejandro; Cau, Miguel Ángel; León, María José
Abstract: This article presents the results of direct accelerator mass spectrometry (AMS) radiocarbon dating of a new bone anvil retrieved in the Iron Age–Roman site of Montefí (Ciutadella), in the southwest of the island of Menorca (western Mediterranean). The radiometric date confirms the chronology obtained through the stratigraphy and typological analysis of ceramics (1st–3rd century AD), and indicates that this bone-made tool not only represents the first archaeological anvil from the island but also constitutes the earliest evidence in the western Mediterranean. This ancient date is more consistent with the known eastern regional chronology and reinforces the importance of obtaining direct AMS 14 C dates to refine artifact chronologies.